PENGARUH VARIETAS DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL PADI SAWAH MENUJU ORGANIK - , GALUH BANOWATI, Prof. Dr. Ir. Tohari, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The rate of increase in productivity of rice nationwide in the last few years tend to ramp (leveling off). Leveling off of rice productivity due to lack of availability of location-specific technologies and technology adoption rates are still relatively low recommended. Application of technology at the farm level is generally from year to year is no different, so a lot of rice cultivation technology components need to be repaired. Meant among other technological improvements is the management of irrigation water, the use of location specific high yielding varieties, setting the optimal spacing, and use of inputs raises the level of environmental health and reduce environmental damage. Fieldwork was carried out by making the research plots in farmers' rice acreage in Dusun Gulon, Desa Srihardono, Kecamatan Pundong, Bantul, Yogyakarta in June - November 2010, to determine the effect of varieties and plant spacing on growth and productivity toward organic lowland system. The treatments are arranged in a complete randomized block design, with 3 blocks as replicates. The first factor is the spacing of treatments, namely: 20 cm x 20 cm, 25 cm x 25 cm, and 30 cm x 30 cm. The second treatment factor was rice varieties, namely: Pandan Wangi as the local varieties, Ciherang and IR-64 as national varieties, as well as Hipa-7 as the hybrid varieties. The results shown by the growth of plant dry weight was highest at plant spacing 20 cm x 20 cm (population 250 000 clumps / ha). Dry weight Pandan Wangi, Ciherang, IR-64 and higher and significantly different than Hipa-7. Dried Grain Milled (MPD) obtained at the highest spacing of 25 cm x 25 cm (population 160 000 clumps / ha), and not significantly different with 20 cm x 20 cm. Dry Milled grain Pandan Wangi, Ciherang, IR-64 higher and significantly different than Hipa-7. Organic farming efforts to obtain high grain yield dry grain milled and have high economic value is the spacing of 25 cm x 25 cm using a variety of Pandan Wangi, although in this study there is no interaction. This is due to the number of seeds used 25 cm x 25 cm up to 36% less than 20 cm x 20 cm, and Pandan Wangi appreciated by the public because of itâs spesific pandan scented. The farmer prefer to plant Pandan Wangi due to itsâs good price.